2016
DOI: 10.1016/j.nicl.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral white matter structure is associated with DSM-5 schizophrenia symptom dimensions

Abstract: Diffusion tensor imaging (DTI) studies have provided evidence of widespread white matter (WM) abnormalities in schizophrenia. Although these abnormalities appear clinically significant, the relationship to specific clinical symptoms is limited and heterogeneous. This study examined the association between WM microstructure and the severity of the five main DSM-5 schizophrenia symptom dimensions. DTI was measured in forty patients with schizophrenia spectrum disorders. Using Tract-Based Spatial Statistics contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 65 publications
1
16
0
1
Order By: Relevance
“…There are ongoing efforts to account for brain heterogeneity by means of delineating patient subtypes 8,55 , as well as characterizing patients by their differential degree of affectedness along one or multiple symptom-axes 11,56 . Here we report that SZ is associated with widespread and increased heterogeneity in cortical thickness, and cortical as well as hippocampal volume, beyond the known mean differences, compared controls.…”
Section: Resultsmentioning
confidence: 99%
“…There are ongoing efforts to account for brain heterogeneity by means of delineating patient subtypes 8,55 , as well as characterizing patients by their differential degree of affectedness along one or multiple symptom-axes 11,56 . Here we report that SZ is associated with widespread and increased heterogeneity in cortical thickness, and cortical as well as hippocampal volume, beyond the known mean differences, compared controls.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, anatomical connectivity values for a range of specific ROI-pairs that were reduced in individuals with schizophrenia were found to be unrelated to the severity of total TD (Skudlarski et al, 2010). Finally, Viher et al (2016) investigated several diffusivity measures within white matter but did not find voxel-clusters that were significantly related to positive TD.…”
Section: White Matter Tracts and Commissuresmentioning
confidence: 89%
“…The relationship of white matter alterations and clinical symptoms in SZ has been examined with inconsistent evidence. Viher et al reported that negative symptoms are related to white matter microstructure of the prefrontal and right temporal lobes, but no association of white matter microstructure and positive symptoms was found [ 86 ]. Conversely, Lener et al showed that lower FA in the genu is associated with greater positive symptom and none of the correlations with negative symptoms are significant [ 31 ].…”
Section: Discussionmentioning
confidence: 99%